Investigations on functional properties of hydrothermally synthesized Ba1-xSrxFe12O19 (x = 0.0 − 0.8) nanoparticles. (May 2019) - Raghuram, N.; Rao, T. Subba; Babu Naidu, K.Chandra
Abstract: The hexagonal Ba1-x Srx Fe12 O19 (x = 0.0, 0.2, 0.4, 0.6 & 0.8) (BSFO) nanoparticles were synthesized by hydrothermal method at low operating temperature of 150 °C/8 h. Latter, the diffraction peaks confirmed the hexagonal structure. The spheres (x = 0.0, 0.2 & 0.6), flat plates (x = 0.4) and rectangular fibers (x = 0.8) like grains were noticed in the microstructure. The transmission electron microscope (TEM) studies revealed the particle diameter (Dp ) changing from ~7–29 nm for all samples. Furthermore, the narrow optical band gap energies (Eg ) were noted to be ~ 2 eV which may be suitable for optoelectronic and photocatalytic applications. Moreover, the temperature dependent ferroelectric behavior of BSFO was examined using polarization versus applied electric field (P-E) loops. The space charge polarization was observed at low frequencies of dielectric constant (ε'), dielectric loss (ε"), ac-conductivity (σac ), dielectric modulus (M' & M"), and impedance (Z' & Z") plots of BSFO. The Arrhenius plots (lnσ versus 10 3 /T) were dawn to find the activation energies (Ea & Eb ). Moreover, the Cole-Cole plots were also drawn as a function of temperature from 313 to 473 K in order to investigate the conduction mechanism through grain/grain boundaries.